A Study on Hedge Funs as An Investment Strategy for Investors: A Qualitative Approach - Jadgev, Simran (2006)
There has been a tremendous growth in the hedge fund industry in terms of size (number of hedge funds) and asset size (hedge fund capital) under their management. This alternative tool of investment that provides high returns at a low degree of risk for investors is still being explored and there are several parameters which affect the growth of this industry which are yet to be researched. This study is written with an aim to provide a deeper insight about hedge fund investing and the factors that affect the investors' decisions and the strategies which are most preferred due to the returns they offer. Data is obtained by adopting a sampling strategy using questionnaires, the answers to which are given by Hedge Fund investors and managers across the 20 hedge funds researched in UK, USA, Australia and India. By examining the feedbacks received, this paper has been able to explore and scrutinize in detail the reason for investors to invest in hedge funds, to be able to provide facts about the real hedge fund practices and the suitable investor profiles. The prime objective of the questionnaire was to assess and understand the different conceptions that both hedge fund investors and managers hold about this tool of investment. The research has not been concluded on a single or a specific result but rather to present an overall view about the research question which was dealt with. It has been able to highlight and comment on the future of hedge fund industry and examine the effectiveness of this financial tool from the investors' point of view.